Ultra-high anisotropic magneto-mechanical damping in Fe-18at.%Ga single crystals. (15th April 2022) - Sun, Meng; Li, Lan; Liu, Caixing; Liu, Xueqing; Jiang, Weibin; Lei, Yawei; Gao, Yunxia; Cheng, Zhijun; Wang, Xianping; Sheng, Zhigao; Wu, Xuebang; Fang, Qianfeng; et al.
Abstract: An ultra-high anisotropic magneto-mechanical hysteresis-type damping (MMHD) with temperature and frequency insensitivity was found in Fe-18at.%Ga single crystals. The [111]-orientated Fe-Ga single crystal exhibits a damping value up to 0.13 (Q −1, equivalent to a special damping capacity SDC of 0.82) in the wide temperature range of −100–150 °C, much higher than that of the conventional ferromagnetic high damping alloys (Fe-Cr/Al based alloys). For the [001]-orientated single crystal however, the MMHD value is almost zero despite the large magnetostrictive coefficient along [001] direction. Through magnetic domain analysis, it is demonstrated that MMHD originates from the stress-induced irreversible movement of 90° domain walls. The MMHD of Fe-Ga single crystals depends positively on the orientation factor, and the ultra-high relaxation strength is closely related to the magnetostriction in the [001] direction and the tetragonal magnetoelastic coupling constant. Graphical abstract: Image, graphical abstract